GAMBARAN EFEK SAMPING KONTRASEPSI SUNTIK PADA AKSEPTOR KB SUNTIK - Sari, Sekar Wulan; Suherni, Suherni; Purnamaningrum, Yuliasti Eka (Jurnal Kesehatan Ibu dan Anak, 2015)
Methods of contraception most widely used in DIY is an injectable and Sleman has the highest number of participants injections inthe province. Injections users based on risk factors according to age and risk factors by parity indicates that there are stiil manyacceptors that do not use contraceptives based on rational contraception usage patterns that will cause various side effects thatmayoccur. This study aimed to describe the side effects of injectable contraceptives in family planning acceptors syringe. This type ofresearch is a descriptive study. The location of research in Kalasan Premier health carewith research subjectswere 41 respondents.The instruments used are questionnaire. Analysis of data using univariate analysis. Characteristics of acceptors by age and paritynot meet rational contraception patterns. Side effects experienced injectable formof family planning acceptorsmenstrual disorders,weight changes, dizziness and headache experienced by the majority of DMPA injectable acceptors.While the majority of the sideeffects of nausea experienced by cyciofeminjectable acceptors.